The Role of Kodam XIV / Hasanuddin Health Team in Natural Disaster Management - Luther Loginsi; Andi Yusuf; Rahmawati Azis; Taufiq Dalming (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
The role of the Kodam XIV / Hasanuddin and TNI health teams in natural disaster management is essential to provide health services and prevent more casualties. However, a deeper understanding of the effectiveness and challenges faced is needed. This study aims to analyze the role of Kodam XIV / Hasanuddin Health in natural disaster management, focusing on mitigation governance, early warning, and disaster preparedness. This research uses qualitative descriptive methods to describe what is happening in the field in related agencies. Data is collected through observation, interviews, and documentation by applying source, data, and time triangulation to ensure the validity and credibility of the information obtained. This research was conducted in West Sulawesi, a province prone to floods, tsunamis, earthquakes, etc. The Health Team of Kodam XIV / Hasanuddin plays an active role in disaster risk management by carrying out mitigation in the form of wave containment infrastructure development and normalization, as well as conducting early warning through the installation of EWS tools controlled by BPBD and BMKG, and conducting training, socialization, and preparing disaster risk reduction plans in the preparedness cycle. It was concluded that the health team of Kodam XIV/Hasanuddin has a central role in disaster risk management by implementing various programs such as mitigation, early warning, and preparedness, as well as providing education and training to the community to increase awareness and response to disasters.